Population genetic structure of Chinese Puccinia triticina races based on multi-locus sequences - Tai-guo LIU; Run-jing GE; Yu-tong MA; Bo LIU; Li GAO; Wan-quan CHEN (Journal of Integrative Agriculture, 2018)
Puccinia triticina, the causal agent of wheat leaf rust, is one of the most devastating rust fungi attacking wheat worldwide. Seventy-six isolates of the wheat leaf rust pathogen from Yunnan, Sichuan, Gansu and Henan provinces, China, were tested on wheat leaf rust differentials and the population structure was analyzed using four presumably neutral partial sequence markers such as elongation factor-1α (EF-1α), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), β-tubulin (TUB) and the second largest RNA polymerase subunit (RPB2). The phenotypic diversity of Yunnan and Sichuan populations was higher than that of Gansu and Henan populations. The four populations were separated into two clusters based on the pathogenic data. A total of 12 single nucleotide polymorphisms (SNPs) and 32 haplotypes were identified among the four sequences. The 32 haplotypes were divided into two clusters in a neighbor-joining tree. Bayesian analyses also identified two clusters. Pairwise FST between populations in different regions were significantly different (P<0.05). Analysis of molecular variance (AMOVA) indicated that 68% of the total genetic variation was within populations.